PENGEMBANGAN KETERAMPILAN LITERASI KEUANGAN ANAK USIA DINI DI SEKOLAH MELALUI MODEL PEMBELAJARAN EXPERIENTAL LEARNING - Fariastuti (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
The development of financial literacy skills from an early age is one of the strategic steps to increase a country's financial literacy index, this is due to the positive correlation between education level and financial literacy and inclusion. The purpose of this study is to describe and analyze the development of early childhood financial literacy skills through experiential learning. This research was conducted at East Purwokerto State Kindergarten, with the research subjects being classroom teachers and students. This research is a field research using a qualitative approach. Data collection was carried out by interview, observation, and documentation techniques. The data is analyzed by means of data reduction, data presentation, and verification and conclusion drawn. The results of this study show that East Purwokerto State Kindergarten implements seven activities with an experiential learning model to develop integrated financial literacy skills through savings activities, infaq movements, currency introduction, visits to Bank Indonesia, market visits, market days, and outing classes. The forms of skills that develop are understanding the function of money, making simple financial decisions, developing financial numeracy, and forming a wise attitude in the use of money